Kajian Pragmatik: Pelanggaran Prinsip Kesopanan dalam Kolom Komentar Instagram Awreceh - Nurfadilla, Nurfadilla; Hasanah, Uswatun; Affani, Nur; Istiqamah, Istiqamah (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to examine violations of the principle of politeness in the Instagram comments column on Awreceh's account. The research method used is a descriptive qualitative method which will explain the research data through detailed descriptions so that it can explain and describe the research results clearly. Data was collected through screenshots of netizens' comments in Awreceh's account posts which were then analyzed according to the principle of politeness theory. Furthermore, from the results of the analysis data were obtained which constitute violations of the maxim of wisdom, violations of the maxim of appreciation, violations of the maxim of sympathy, and violations of the maxim of suitability. Keywords: Awreceh, Instagram, Violation of the Principle of Politeness, Netizens.